RELATIONSHIP BETWEEN ORGANIZATIONAL CULTURE AND CORPORATE SUSTAINABILITY - Filipova, Milena; Gârdan, Iuliana Petronela; Bondrea, Aurelian; Gârdan, Daniel (Annals of Spiru Haret University. Economic Series, 2024)
In an era marked by increasing concern for the environment and a drive to improve corporate performance, the interplay between sustainability and organizational performance has emerged as a major focal point for businesses. Businesses, as integral components of a global economy, face the dual challenge of addressing complex sustainability imperatives while striving to improve organizational culture, the collective values, norms and beliefs that shape the behavior and decisions of individuals within the enterprise. The extent to which businesses adopt and cultivate a culture that prioritizes sustainability initiatives while promoting efficiency and innovation can profoundly affect their prospects in today’s dynamic business environment. The purpose of this paper is to establish the relationship between corporate sustainability and organizational culture, exploring how the conscious integration of sustainability values and principles into an enterprise’s culture can provide significant opportunities not only to mitigate adverse environmental impacts, but also to improve performance of the organization. The main research methods involved in the development are content analysis, method of analysis and synthesis, method of observation, intuitive and systematic approach. The expected results of the development identified key aspects of the relationship between organizational culture and corporate sustainability.